Neighborhood Immigrant Density and Population Health among Native-Born Americans - Shi, Lu (Prev Med, 2019)
The healthy immigrant effect—where immigrants are on average healthier than the native born— have been well studied. However, little is known about the relationship between immigration and the health of the native born. This study fills this important research gap by examining the association between neighborhood immigrant density and several population health measures among native-born Americans. We used data from the Los Angeles County Health Survey to analyze four individual-level health behaviors and outcomes, including regular fast food consumption, fruit and vegetable consumption, body mass index, and hypertension. We conducted multilevel logistic regressions to assess the association between neighborhood immigrant density and the four health behaviors and outcomes. The results showed that neighborhood immigrant density was negatively associated with regular fast food consumption (OR=0.33; 95% CI, 0.18–0.59), BMI (β= −2.16, 95% CI, −3.13 - −1.19), and hypertension (OR=0.58; 95% CI, 0.38–0.89), and positively associated with fruit/vegetable consumption (OR=1.64; 95% CI, 1.01–2.66) among native-born Americans. In conclusion, native-born Americans who live in a neighborhood with a high density of immigrants had healthier behaviors and better health outcomes compared to those who live in a neighborhood with a low density of immigrants.